Distribution and Types of Microplastics in Coastal Sediments of Sepanjang Beach - Indriani, Risda Putri; Mahardika, Reza Dino; Oetari, Feni; Rusdi, Rusdi; Isfaeni, Hanum (Sriwijaya Journal of Environment, 2025)
Microplastic waste has polluted Indonesian waters, especially at Sepanjang Beach. Microplastics that are not handled properly can enter the digestive tract of aquatic animals, one of which is gastropods. The presence of microplastics must be identified in the gastropod digestive tract, considering that gastropods are also a food ingredient. Sampling was done by purposive sampling and quadratic transects. The length of the transect used is 50m perpendicular to the beach with a quadrant plot measuring 1x1 m. In each plot, 1 individual was taken for each species found. Sample preparation using 15 ml of 10% KOH solution and incubated for 1 night. Optical analysis of microplastics using a stereo microscope at 40x magnification. The most microplastics were found in the Turbo setosus species with 701 particles. The most common form of microplastic found in Gastropods and Bivalvia in the sample was fiber with a total of 2204 particles. Microplastics were also found in seawater on the beach with the form of fiber being the most commonly found, namely as many as 553 particles.